Avaliação dos fatores de influência na implementação e no desempenho acadêmico do Câmpus São José dos Campos do IFSP - Novais, Natália Helena dos Santos (Universidade Federal de São Carlos, 2017)
Education is at the heart of the State's concerns, given its essential role in the development of a country. In the last years, the public policy that has stood out in the education is the creation / transformation of the Federal Institutes of Education, Science and Technology (IF's). The creation of these institutions opened space for the discussion of IF’s as public educational policy, making clear the need to analyze how effective the application of such policy has been. It is in this context that the present research is inserted, which to analyze the implementation process of the Campus of the Federal Institute of São Paulo in São José dos Campos. At the outset, a brief bibliographical review was made on the following points: public policies and implementation of public policies, on the historical process of creation of the federal institutes, highlighting the guiding elements of this process, and on the networks and the implementation of the policy of vocational education. In a second moment, the case study itself is presented, that is the implementation process of Campus São José dos Campos and its specificities. Subsequently, the data obtained through the application of questionnaires and interviews were presented and discussed. Finally, the final considerations were exposed, highlighting the existence of a low interaction of the Campus actors with the external community, a factor that may hinder the development of their activities. It is suggested, among other aspects, the establishment of partnerships and the holding of meetings and events outside the unit to order to establish a closer relationship with the community and reduce the difficulties faced in relation to its location.
Evaluation of the influence factors in the implementation and academic performance of São José dos Campos campus of IFSP
Keywords: Políticas públicas; Implementação; Redes; Institutos Federais; Educação; Public policies; Implementation; Networks; Federal Institutes; Education; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE UNIDADES EDUCATIVAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS::ANALISE INSTITUCIONAL